2020
DOI: 10.1055/s-0039-1700445
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Thumb Duplication: A Systematic Review of Surgical Techniques

Abstract: Surgical intervention for thumb duplication can be divided into three categories: simple excision of the accessory thumb, excision of the accessory thumb with reconstruction from available “spare parts,” and combining the two thumbs into one, as described by Bilhaut. This prospectively PROSPERO registered systematic review evaluates the overall, aesthetic and functional outcomes for the latter two options (reconstruction from spare parts vs. combining two thumbs into one), aiming to facilitate evidence-based d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…The choice of treatment varies depending on the anatomy of the extra thumb connected to the main thumb, which is consistent with the view of previous reports ( 10 , 11 , 24 – 27 ). Tada et al and Kim et al reported that an extra thumb connected to the main thumb by soft tissue alone should be classified as an independent subtype ( 24 , 25 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The choice of treatment varies depending on the anatomy of the extra thumb connected to the main thumb, which is consistent with the view of previous reports ( 10 , 11 , 24 – 27 ). Tada et al and Kim et al reported that an extra thumb connected to the main thumb by soft tissue alone should be classified as an independent subtype ( 24 , 25 ).…”
Section: Discussionsupporting
confidence: 88%
“…For example, in C type, the extra thumb can be connected to the main thumb by bifurcated phalanx at the level of the distal phalanx, proximal phalanx or bifurcated metacarpus. Flap design, muscle tendon and bone reconstruction are different depending on the duplication level ( 27 , 28 ). Therefore, it is necessary to explore a simple and comprehensive classification system useful for selecting the best treatment option ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“… 20 Furthermore, joint stiffness, marked broadness, and conspicuous scarring of the nail bed and pulp are noted drawbacks of the Bilhaut-Cloquet procedure, which has largely fallen out of favor because of poor outcomes and cosmesis; it often produces a wide, stiff thumb, being now used only for very distal duplications. 9 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…The aim of the treatment is to achieve function nearly normal as possible, with good thumb joint stability, mobility, and strength, while providing an acceptable esthetic appearance. 8 , 9 Considerations prior to surgical intervention include analysis of patient’s bony anatomy, hand physical examination, including thumb alignment, tendons, range of motion, joint stability, and family counseling (particularly asymmetry in thumb size). 10…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation